Addressing Dilemmas of Social Justice Mathematics through Collaboration of Students, Educators, and Researchers - Kari Kokka (Educational Considerations, 2015)
In this paper, I provide a definition of Social Justice Mathematics. I explore three dilemmas that arise with SJM instruction and suggest ways in which collaboration among students, educators, and researchers may address these dilemmas.
Keywords: Social Justice; instruction; collaboration; Students; educators; researchers; Rigorous mathematics; success; dominant; socioeconomic; classroom